2020
DOI: 10.1007/s11548-020-02165-4
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal mixed reality visualisation for intraoperative surgical guidance

Abstract: Purpose In the last decade, there has been a great effort to bring mixed reality (MR) into the operating room to assist surgeons intraoperatively. However, progress towards this goal is still at an early stage. The aim of this paper is to propose a MR visualisation platform which projects multiple imaging modalities to assist intraoperative surgical guidance. Methodology In this work, a MR visualisation platform has been developed fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 15 publications
0
38
0
1
Order By: Relevance
“…Although the use of augmented reality technology for teaching remains relatively new, benefits have already been identified from using the HoloLens for medical use, such as for visualising organs prior to surgery (Cartucho, Shapira, Ashrafian, & Giannarou, 2020), teaching dental students (Zafar & Zachar, 2020) and in pathology education (Hanna, Ahmed, Nine, Prajapati, & Pantanowitz, 2018). However, this technology has not yet been commonly utilised in the tertiary medical or health education environments.…”
Section: Introductionmentioning
confidence: 99%
“…Although the use of augmented reality technology for teaching remains relatively new, benefits have already been identified from using the HoloLens for medical use, such as for visualising organs prior to surgery (Cartucho, Shapira, Ashrafian, & Giannarou, 2020), teaching dental students (Zafar & Zachar, 2020) and in pathology education (Hanna, Ahmed, Nine, Prajapati, & Pantanowitz, 2018). However, this technology has not yet been commonly utilised in the tertiary medical or health education environments.…”
Section: Introductionmentioning
confidence: 99%
“…The 3D models displayed by HL can be manipulated at any time by the surgeon's own hands while wearing sterile gloves and can be viewed from any angle without changing the standing position of the surgeon. 11,13 Moreover, because the 3D model can be displayed freely in all directions, not only in the surgical field, surgeons can check the anatomy side by side with the 2D image or can display the 3D model next to the laparoscopic view during surgery and check the anatomy while comparing them, similar to a car navigation system. Therefore, the time spent referring to images may have become greater than that spent referring to conventional images, leading to a prolonged operative time.…”
Section: Discussionmentioning
confidence: 99%
“…This reinforces the surgeons' spatial awareness, making it possible to understand the anatomy more intuitively, compared with conventional 2D images presented on a monitor. Cartucho et al 13 compared 2D images and 3D models displayed by a wearable mixed-reality device and reported that the 3D models were more highly evaluated by the surgeons. As surgeons with less surgical experience evaluated 3D models more highly than experienced surgeons, 10,14 we speculate that less experienced surgeons with lower spatial awareness may benefit more from 3D models.…”
Section: Discussionmentioning
confidence: 99%
“…The sample entropy expression is defined as S ( x , y ) for an embedding dimension of m and a similarity threshold of y . Thus, for an EEG time series of time length T , the dynamic sample entropy expression is shown in the following equation, where the subscript k represents the sliding time window [ 26 ]: …”
Section: Cognitive Computing Of Brain Metabolism In Maintenance Hemodialysis Patients With Multimodal Mri Studymentioning
confidence: 99%